Geometry Learning through GeoGebra in Mathematics Education: Trends, Effects, and Research Gaps (2020–2025) - Nur Fitriyana; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Ely Susanti (AL-ISHLAH: Jurnal Pendidikan, 2026)
Geometry is fundamental in mathematics education for developing spatial reasoning and understanding abstract relationships. However, students often struggle with its abstract nature. Dynamic geometry software such as GeoGebra offers interactive visualization that can enhance conceptual understanding. This study aims to examine research trends, instructional strategies, and gaps in GeoGebra-based geometry learning.A systematic literature review (SLR) was conducted following PRISMA guidelines, complemented by bibliometric analysis using VOSviewer. From an initial pool of 119 studies published between 2020 and 2025, 15 articles were selected based on predefined inclusion criteria. The selected studies were analyzed to identify patterns in pedagogy, outcomes, and research focus.The findings indicate that GeoGebra effectively supports innovative instructional approaches, including project-based learning, problem-based learning, and flipped learning. Its use significantly improves students’ conceptual understanding of geometry, particularly in topics such as geometric transformations. Additionally, GeoGebra enhances students’ motivation, confidence, and engagement in learning mathematics.Despite these benefits, the integration of GeoGebra with culturally contextualized learning remains limited. Few studies address basic geometric concepts, such as lines and angles, within local cultural contexts (e.g., traditional dance patterns), indicating an underexplored area in current research.GeoGebra is a powerful tool for enhancing geometry learning; however, future research should focus on developing culturally responsive, technology-integrated approaches to bridge existing gaps and enrich mathematics education.